ECB policy facilitating corporate financing in the green bond market - Franziska Bremus; Franziska Schütze; Aleksandar Zaklan (DIW Weekly Report, 2021)
The green bond market has grown strongly in recent years, especially in the euro area. With regard to the European Union's climate targets, it is likely that the demand for green bonds-bonds that specifically support sustainable projects-will continue to increase in the future. The European Central Bank (ECB) is buying green bonds as well and is planning to reorient its strategy towards more sustainability. This Weekly Report presents an empirical analysis of the evolution of the rapidly evolving green bond market. In addition, the effect of ECB bond purchases on yields under the corporate sector purchase program (CSPP) and the pandemic emergency purchase program (PEPP) is examined. The analysis shows that ECB bond purchases improve financing conditions also for corporate green bond issuers. One decisive criterion for whether a bond may be purchased by the ECB is its credit rating. Currently, the climate-related risks for firms are not sufficiently considered in credit ratings and the advantages of green bonds receive little attention compared to conventional bonds as a result. Improved mapping of climate-related risks into credit ratings would not only be important for market stability, but could also further improve financing conditions for green bond issuers.
Keywords: E52; E58; G12; G18; Q54; 330; green bonds; bond yields; monetary policy; corporate sector purchase programme (CSPP); pandemic emergency purchase programme (PEPP)